The Impact Of Teaching According To Design Thinking On The Metacognitive Awareness Of Fifth Grade Female Students (Journal of the College of Basic Education, 2024)
The aim of this research is to determine the "impact of teaching using design thinking on metacognitive awareness among fifth-grade female students." The researcher used an experimental design with partial control of two groups (experimental and control) with a post-test for metacognitive awareness scale. The research population included all fifth-grade female students in the government daytime girls' schools affiliated with the Directorate of Education in Al-Rusafa Second in Baghdad - Al-Markaz. The school was intentionally chosen to represent the research sample, with a total of (53) students. Section (A) was selected to represent the experimental group, consisting of (28) students, while section (B) was chosen to represent the control group, consisting of (25) students. The experiment was conducted in the second semester of the academic year (2023-2024),The researcher ensured equivalence between the students in the experimental and control groups in some variables that may affect the experiment results, including chronological age, pre-knowledge test in science, Raven's intelligence test, previous science achievement, parents' educational attainment, and metacognitive awareness. The scientific material was selected from the fourth and fifth units of the seventh revised edition (2023) of the science textbook for the fifth grade. Behavioral objectives were formulated for the two units, totaling (188) behavioral objectives according to Bloom's taxonomy classification for the cognitive domain levels (remembering, understanding, applying, analyzing, synthesizing, evaluating),To achieve the research objective, the researcher developed a research tool, which is the Metacognitive Awareness Scale consisting of (40) items distributed across eight components. The scale was subjected to content validity by experts in measurement, evaluation, and psychology. It was also applied to a pilot sample to verify construct validity and to extract psychometric properties. Additionally, the reliability coefficient of the scale was calculated using Cronbach's alpha, and its value was (0.927), The researcher applied the Metacognitive Awareness Scale to the research groups after completing the experiment, which lasted for (9) weeks. Data analysis was conducted statistically using the independent samples t-test and relied on the Statistical Package for the Social Sciences (SPSS) and Microsoft Excel. The results showed that the students in the experimental group, who were taught using design thinking, outperformed the students in the control group, who were taught using the traditional method, in metacognitive awareness with a statistically significant difference and a large effect size, Based on the research results, the researcher made a series of recommendations and suggestions, which were presented in the fourth chapter.